2017
DOI: 10.1371/journal.ppat.1006401
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of IL-12p70 formation by IL-2 or following macrophage depletion causes T-cell autoreactivity leading to CNS demyelination in HSV-1-infected mice

Abstract: We have established two mouse models of central nervous system (CNS) demyelination that differ from most other available models of multiple sclerosis (MS) in that they represent a mixture of viral and immune triggers. In the first model, ocular infection of different strains of mice with a recombinant HSV-1 that expresses murine IL-2 constitutively (HSV-IL-2) causes CNS demyelination. In the second model, depletion of macrophages causes CNS demyelination in mice that are ocularly infected with wild-type (WT) H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In addition, the levels of P-selectin and IL-12p70 were not significantly different among the GN-BSI, GP-BSI and fungal-BSI patients ( P > .05), despite that previous studies have occasionally reported that P-selectin and IL-12p70 play an important role in the regulating immune activation and participating in inflammatory response when infection occurs. [36,37] Similar investigations of these factors need to be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the levels of P-selectin and IL-12p70 were not significantly different among the GN-BSI, GP-BSI and fungal-BSI patients ( P > .05), despite that previous studies have occasionally reported that P-selectin and IL-12p70 play an important role in the regulating immune activation and participating in inflammatory response when infection occurs. [36,37] Similar investigations of these factors need to be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…They believe that it plays a crucial role in sustaining hypo-immune phenotype leading to chronic deteriorations. Another study showed that a suppression of IL-12p70, and not other members of IL-12 family, is linked to demyelination while an increase in IL-12p70 reversed the process (Lee et al, 2017 ). Interestingly, IL-12 family including IL-12p70 are important for the activation of IFN-γ supporting a strong link between the two in inflammation (Gee et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies with animal models showed latent TG infections and demyelinating lesions in mice intranasally infected with HSV-1 [ 107 ]. Later research also reported that mice infected with HSV-1 can develop lethal encephalitis or virus-induced CNS multifocal demyelinating lesions, with outcome affected by several factors, including the route of infection and mouse strain [ 108 , 109 , 110 , 111 , 112 ]. Demyelinating lesions have also been associated with HSV-1-induced facial nerve paralysis [ 113 ].…”
Section: Hsv-1 and Demyelinationmentioning
confidence: 99%